Operationality of concepts in Heideggerian phenomenological investigation: epistemological reflection on Nursing - Thaís Vasconselos Amorim; Ívis Emília de Oliveira Souza; Anna Maria de Oliveira Salimena; Stela Maris de Mello Padoin; Rita de Cássia de Jesus Melo
ABSTRACT Objective: To describe the investigative path of analysis and the operationality of concepts based on Martin Heidegger's theoretical and philosophical framework. Method: Theoretical reflection on the phenomenon of pregnancy in a woman with heart disease. Results: Stages of the investigative movement were evidenced based on the pre-reflection related to the object of study and to the search for the phenomenal meaning, using the existential and analytical Hermeneutics as the approach and resulting in the reach of the phenomenal totality. Conclusion: The worldview of the researcher, who considered the subjectivities of the person in a health or disease situation, favored the announcement of the referential by the object of study. Knowledge production in the light of Martin Heidegger's phenomenology unveiled phenomena lived and experienced in the Health and Nursing field, provided of epistemological rigor that demanded appropriation of concepts inherent to the existential analytics.